Ledipasvir/sofosbuvir regimens for chronic hepatitis C infection: Insights from a work productivity economic model from the United States. Issue 5 (23rd March 2015) - Younossi, Zobair M.; Jiang, Yushan; Smith, Nathaniel J.; Stepanova, Maria; Beckerman, Rachel
Abstract : Patients with chronic hepatitis C (CHC) exhibit reduced work productivity owing to their disease. Historically, most regimens indicated for CHC genotype 1 (GT1) patients were administered with pegylated interferon (Peg‐IFN) and/or ribavirin (RBV), which further compromised work productivity during treatment. The aim of this study was to model the impact of LDV/SOF (ledipasvir/sofosbuvir), the first Peg‐IFN‐ and RBV‐free regimen for CHC GT1 patients, on work productivity from an economic perspective, compared to receiving no treatment. The WPAI‐SHP (Work Productivity and Activity Index–Specific Health Problem) questionnaire was administered to patients across the ION clinical trials (N = 1, 923 U.S. patients). Before initiation of treatment, patients with CHC GT1 in the ION trials exhibited absenteeism and presenteeism impairments of 2.57% and 7.58%, respectively. Patients with cirrhosis exhibited greater work productivity impairment than patients without cirrhosis. In total, 93.21% of U.S. patients in the ION trials achieved SVR; these patients exhibited absenteeism and presenteeism impairments of 2.62% ( P  = 0.76, when compared to baseline) and 3.53% ( P  < 0.0001), respectively. Monetizing these data to the entire U.S. population, our model projects an annual societal cost of $7.1 billion owing to productivity loss in untreated GT1 CHC patients. Our model projects that, when compared to no treatment, treating all CHC GT1 patients with a regimen with very high viral eradication rates (LDV/SOF) would translate to annual productivity loss savings of $2.7 billion over a 1‐year time horizon. Conclusions : Patients with untreated HCV impose a substantial societal burden owing to reduced work productivity. As a result of improvements in work productivity, treatment of CHC GT1 patients with LDV/SOF‐based regimens is likely to result in significant cost savings from a societal perspective, relative to no treatment. (Hepatology 2015;61:1471–1478)